2008
DOI: 10.1016/j.neuro.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental effects of maternal nutritional status and exposure to methylmercury from eating fish during pregnancy

Abstract: Fish contain nutrients that promote optimal brain growth and development but also contain methylmercury (MeHg) that can have toxic effects. The present study tested the hypothesis that the intake of selected nutrients in fish or measures of maternal nutritional status may represent important confounders when estimating the effects of prenatal methylmercury exposure on child development. The study took place in the Republic of Seychelles, an Indian Ocean archipelago where fish consumption is high. A longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 45 publications
10
168
4
Order By: Relevance
“…Lederman et al (2008) observed a decrease in the motor activity (PDI) in children tested after 36 and 48 months, but not at earlier time points. Similar findings were reported from Seychelles children exposed to higher methyl mercury levels (MH 5.6 µg/g): A negative association of methyl mercury and PDI was observed in children at the age of 30 months but not in children investigated at the age of 9 months (Davidson et al, 2008b;Strain et al, 2008). Jedrychowski et al (2006; only observed a significant effect in 12 month old children, but not in older ones.…”
Section: Study Locationsupporting
confidence: 87%
See 1 more Smart Citation
“…Lederman et al (2008) observed a decrease in the motor activity (PDI) in children tested after 36 and 48 months, but not at earlier time points. Similar findings were reported from Seychelles children exposed to higher methyl mercury levels (MH 5.6 µg/g): A negative association of methyl mercury and PDI was observed in children at the age of 30 months but not in children investigated at the age of 9 months (Davidson et al, 2008b;Strain et al, 2008). Jedrychowski et al (2006; only observed a significant effect in 12 month old children, but not in older ones.…”
Section: Study Locationsupporting
confidence: 87%
“…However these studies suggest an attenuating effect of polyunsaturated fatty acids to adverse effects of MeHg Analysis of these data (Davidson et al, 2008b;Strain et al, 2008) by longitudinal analysis (allowing for different covariate effects at different time points) confirmed the former results .…”
Section: Controlledsupporting
confidence: 61%
“…Of 20 previous studies using the BSID (Davidson et al 1995(Davidson et al , 2008Jedrychowski et al 2006Jedrychowski et al , 2007Lederman et al 2008;Plusquellec et al 2010;Stokes-Riner et al 2011;Llop et al 2012;Watson et al 2012;Valent et al 2013;Boucher et al 2014;Hsi et al 2014;Strain et al 2015;Marques et al 2015Marques et al , 2016aRothenberg et al 2016;Julvez et al 2016;Prpić et al 2017), 11 reported adverse effects of methylmercury on the PDI, and three observed such effects on the MDI; that is, these rates of 11/20 and 3/20 differed significantly (Fisher exact test, P = 0.019). Thus, psychomotor development appeared to be more susceptible to methylmercury than mental development.…”
Section: Discussionmentioning
confidence: 88%
“…The Faroese birth cohort study demonstrated the impacts of prenatal methylmercury exposure on neurodevelopmental disorders such as sensory deficits, motor impairment, and an overall cognitive decline (Grandjean et al 1997;Debes et al 2006). Regarding the adverse effects of methylmercury on other functions, a variety of results were obtained from previous research using, for instance, the Bayley Scales of Infant Development (BSID) consisting of mainly the mental and psychomotor developmental indices (MDI and PDI, respectively); some studies reported the impact of methylmercury on the MDI (Jedrychowski et al 2006;Rothenberg et al 2016;Marques et al 2016a) and others described the effect on the PDI (Davidson et al 1995(Davidson et al , 2008Jedrychowski et al 2006Jedrychowski et al , 2007Lederman et al 2008;Stokes-Riner et al 2011;Llop et al 2012;Hsi et al 2014;Marques et al 2015;Strain 2015;Prpić et al 2017). Only one report demonstrated that prenatal methylmercury exposure affected both the MDI and PDI (Jedrychowski et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Second, in Massachusetts, USA, higher mercury levels of maternal hair (the range of maternal hair mercury = 0.02-2.38 ppm) were associated with lower infant cognition at 6 months of age (Oken et al 2005). Third, in Seychelles, an Indian Ocean archipelago, neurodevelopmental performance at 30 months infants decreased with increased methylmercury exposure (mean maternal hair methylmercury = 5.9 ppm), although in the initial studies (Davidson et al 1998;Myers et al 2003), no effects were observed Decreases rate of fertility in both males and females, and birth of abnormal offspring (Davidson et al 2008). Lastly, in Italy, mercury in hair of 7-year-old children was fairly correlated with mercury in maternal hair at delivery and was strongly correlated with child's seafood consumption.…”
Section: Bioaccumulation Of Mercury and Effects On Public Healthmentioning
confidence: 92%